Safety and Feasibility of Magnetic Resonance Imaging of the Brain at 1.5 Tesla in Patients with Temporary Transmyocardial Pacing Leads - Homsi, Rami; Mellert, Fritz; Luechinger, Roger; Thomas, Daniel; Doerner, Jonas; Luetkens, Julian; Schild, Hans H.; Naehle, Claas P. (The Thoracic and Cardiovascular Surgeon, 2019)
Background Temporary transmyocardial pacing leads (TTPLs) represent an absolute contraindication to magnetic resonance imaging (MRI). The purpose of this study was to evaluate the safety and feasibility of MRI at 1.5 Tesla (T) using a transmit/receive (T/R) head coil in patients with TTPL.Methods TTPLs (220 cm, Osypka TME, Dr. Osypka GmbH, Rheinfelden, Germany) were implanted in a phantom and exposed to conditions of a 1.5 T brain examination using a T/R head coil. Temperature changes at the lead tip were continuously recorded. A total of 28 patients with TTPL and an urgent indication for a brain MRI underwent MRI at 1.5 T with vital sign monitoring. A T/R head coil was used to minimize radiofrequency exposure of the TTPL. Before and immediately after the MRI scan, TTPL lead impedance, pacing capture threshold (PCT), signal slope, and sensing were measured. Serum troponin I was determined before and after MRI to detect thermal myocardial injury.Results In vitro, the maximum temperature increase from radiofrequency-induced heating of the TTPL tip was < 1°C. In vivo, no complications, such as heating sensations, dizziness, unexpected changes in heart rate or rhythm, or other unusual signs or symptoms were observed. No significant changes in the lead impedance, PCT, signal slope, or sensing were recorded. There were no increases of serum troponin I after the MRI examination.Conclusions MRI of the brain may be performed safely at 1.5 T using a T/R head coil in case of an urgent clinical need in patients with TTPL and may be considered a feasible and safe procedure when appropriate precautionary measures are taken.
Keywords: temporary transmyocardial pacing leads; pacing; magnetic resonance imaging; brain; transmit/receive coil; MRI safety